Redistricting and Electoral Integrity: Institutional Dynamics and Political Inequality in Banyuwangi - Heniwati Heniwati; Kris Nugroho (Pencerah, 2025)
This study aims to analyze the institutional design for delineating electoral districts (daerah pemilihan) in elections and its implications for achieving electoral integrity in Banyuwangi Regency. It focuses on examining the extent to which the principles of electoral districting and seat allocation are fulfilled during redistricting processes, and identifying the appropriate institutional framework to ensure fair and sustainable electoral arrangements. Employing a qualitative method with a field research approach, this study was conducted in Banyuwangi Regency, Indonesia. The findings reveal that the redistricting process, which resulted in the addition of new electoral districts, disproportionately benefits larger and institutionally entrenched political parties. These parties are more capable of adapting to changes in seat allocation and capitalizing on newly formed districts, leading to increased electoral advantages. Moreover, redistricting introduces uncertainties in vote distribution, influences candidate recruitment mechanisms, and impacts the consolidation of party systems. The study also found that the decision of the national electoral commission (KPU) to adopt the third districting proposal, despite public preference for the 2019 configuration, lacked transparency and reflected political lobbying. This undermines the principle of continuity in electoral design. Consequently, this research underscores the need for a reformed institutional structure that ensures participatory, consistent, and integrity-driven electoral districting processes.